International Journal of Agriculture and Natural Resources 2020
DOI: 10.7764/ijanr.v47i2.1971
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of Melanaphis donacis (Hemiptera: Aphididae) and its Coccinellidae and Syrphidae predators on Arundo donax L.

Abstract: N. Undurraga, J.E. Araya, F. Zuazúa, and M.F. Alonso. 2020. Population dynamics of Melanaphis donacis (Hemiptera: Aphididae) and its Coccinellidae and Syrphidae predators on Arundo donax L. Int. J. Agric. Nat. Resour. 117-125. The population density of the aphid Melanaphis donacis (Passerini) was studied in experimental plots of Arundo donax (L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…and Syrphidae larvae. Several studies recorded the importance of Chrysopidae and Syrphidae as predators for aphids (Chambers & Adams 1986;White et al 1995;El-Hag et al 1996;Fonseca et al 2000;Slman 2006;Bugg et al 2008;Saleem et al 2009;Adnan & Khan 2017;Shaukat 2018;Undurraga et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Syrphidae larvae. Several studies recorded the importance of Chrysopidae and Syrphidae as predators for aphids (Chambers & Adams 1986;White et al 1995;El-Hag et al 1996;Fonseca et al 2000;Slman 2006;Bugg et al 2008;Saleem et al 2009;Adnan & Khan 2017;Shaukat 2018;Undurraga et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example, providing flowering plants which include a floral nectar and extra-floral secretions could increase pest parasitism rates because these food resources represent a food for parasitoid adults (Barbosa 1998;Begg et al 2017). Also, the positive effect of aphidophagous predators on controlling cereal aphids within wheat crop has been reported by many researchers (Chambers & Adams 1986;White et al 1995;El-Hag et al 1996;Fonseca et al 2000;Slman 2006;Bugg et al 2008;Saleem et al 2009;Inayat et al 2011;Adnan & Khan 2017;Arshad et al 2018;Shaukat 2018;Kök et al 2020;Undurraga et al 2020). Generalist predators epitomize the most abundant and their role on suppressing cereal aphids has been observed in field settings (Alderweireldt 1994;Bilde & Toft 2001;Harwood et al 2004;Khan 2016;Schmidt et al 2003;Sunderland et al 1987;Sunderland & Vickerman 1980;Upadhyay et al 2020).…”
Section: Introductionmentioning
confidence: 96%
“…Surveys in California indicated that it is a host plant for the blue-green sharpshooter [Graphocephala atropunctata (Signoret); Hemiptera: Cicadellidae], which can vector the bacterium that causes Pierce's disease of grapes (Vitis vinifera L. or other species/hybrids) (Herrera and ). An adventive leaf-feeding aphid [Melanaphis donacis (Passerini); Hemiptera: Aphididae] is known from California (Dudley et al 2008), South America (Underraga et al 2020), and South Africa (Canavan et al 2019) and is spreading invasively in the native range of A. donax in Pakistan (Amin et al 2019), where it is considered a pest on that plant as well as on common reed [Phragmites australis (Cav.) Trin.…”
Section: Importancementioning
confidence: 99%
“…Another insect herbivore, the aphid Melanaphis donacis (Passerini) (Hemiptera; Aphididae), is widespread in the invaded range of Ar. donax in California, as well as in Chile, and has modest impacts when present at high densities on leaf blades [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%